Comparison of free high resolution digital elevation data sets (ASTER GDEM2, SRTM v2.1/v4.1) and validation against accurate heights from the Australian National Gravity Database - Rexer, Moritz; Hirt, Christian (Taylor & Francis Co Ltd, 2014)
Today, several global digital elevation models (DEMs) are freely available on the web. This study compares and evaluates the latest release of the Advanced Spaceborne Thermal Emission Reflectometer DEM (ASTER GDEM2) and two DEMs based on the Shuttle Radar Topography Mission (SRTM) as released by the United States Geological Survey (SRTM3 USGS version 2.1) and by the Consortium for Spatial Information (SRTM CGIAR-CSI version 4.1) over the Australian continent. The comparison generally shows a very good agreement between both SRTM DEMs; however, data voids contained in the USGS model over steep topographic relief are filled in the CGIAR-CSI model. ASTER GDEM2 has a northeast- to southwest-aligned striping error at the 10 m level and shows an average height bias of –5 m relative to SRTM models. The root-mean square (RMS) height error obtained from the differences between ASTER GDEM2 and SRTM over Australia is found to be around 9.5 m. An external validation of the models with over 228 000 accurate station heights from the Australian National Gravity Database allows estimating each models’ elevation accuracies over Australia: ASTER GDEM2 ~ 8.5 m, SRTM3 USGS ~ 6 m, SRTM CGIAR-CSI ~ 4.5 m (RMS). In addition, the dependence of the DEM accuracy on terrain type and land cover is analysed. Applying a cross-correlation image co-registration technique to 529 1 × 1 degree tiles and 138 2 × 2 degree tiles reveals a mean relative shift of ASTER GDEM2 compared with SRTM of –0.007 and –0.042 arc-seconds in north–south and –0.100 and –0.136 arc-seconds in east–west direction over Australia, respectively.